INEQUALITIES FOR HYPO-q-NORMS ON A CARTESIAN PRODUCT OF INNER PRODUCT SPACES - Dragomir, Silvestru Sever (Matematichki Bilten, 2019)
In this paper we introduce the hypo-\(q\)-norms on a Cartesian product of inner product spaces. A representation of these norms in terms of inner products, the equivalence with the \(q\)-norms on a Cartesian product and some reverse inequalities obtained via the scalar Shisha-Mond, Birnacki et al., Grüss type inequalities, Boas-Bellman and Bombieri type inequalities are also given.